Aberrant TGF-β1 signaling activation by MAF underlies pathological lens growth in high myopia - Xiangjia Zhu (Nature Portfolio, 2021)
High myopia is associated with lens changes, but the underlying mechanisms are unclear. Here, the authors show increased equatorial diameter of the lens in subjects affected by high myopia, and find that these changes are associated with an increase in crystallin expression driven by the transcription factor MAF and TGF-β1 signaling.